(untitled) (Progressive Agriculture, 2013)
Five plant extracts viz. garlic tablet, allamanda tablet, neem leaf extract, bishkatali leaf extract and zinger rhizome extract were assessed as seed treating agents against seed-borne pathogens of jute. Farmers seeds carry seed-borne fungi and their prevalence varies in varieties and locations. Garlic tablet was effective in controlling seed-borne fungal infection; consequently the seed germination was high. The effect of allamanda tablet was similar to that of garlic tablet. Neem leaf extract was able to reduce seed-borne fungi but the other three extracts were not effective in controlling seed-borne infection. The performance of garlic tablet was similar to that of Vitavax-200. A significant increase in seedling vigor was also observed over untreated control after garlic treatment. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16461 Progress. Agric. 22(1 & 2): 1 10, 2011